2016
DOI: 10.3892/or.2016.5073
|View full text |Cite
|
Sign up to set email alerts
|

Lapatinib-resistant cancer cells possessing epithelial cancer stem cell properties develop sensitivity during sphere formation by activation of the ErbB/AKT/cyclin D2 pathway

Abstract: Lapatinib, a dual inhibitor of epidermal growth factor receptor (EGFR)/ErbB2, has antiproliferative effects and is used to treat patients with ErbB2-positive metastatic breast cancer. In the present study, we examined the effects of lapatinib on growth of oral and prostate cancer cells. Oral squamous cell carcinoma (OSCC) cell lines HSC3, HSC4 and Ca9-22 were sensitive to the antiproliferative effects of lapatinib in anchorage-dependent culture, but the OSCC cell lines KB and SAS and the prostate cancer cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 36 publications
(35 reference statements)
0
23
0
Order By: Relevance
“…This suggests that lapatinib does not suppress BCSC self-renewal, but may inhibit proliferation of differentiated tumor cells regardless of HER2 status [67]. A recent study reports that a lapatinib-resistant oral squamous cell carcinoma cell line SAS develops sensitivity to lapatinib during sphere-formation through the activation of HER2/AKT/Cyclin D2 pathway [68]. Induced lapatinib resistance in HER2+ BC cells also shows an up-regulated Snail and Vimentin and down-regulated E-cadherin, therefor increasing intrinsic EMT capability [69].…”
Section: Her2 Blockade May Target Bcscsmentioning
confidence: 99%
“…This suggests that lapatinib does not suppress BCSC self-renewal, but may inhibit proliferation of differentiated tumor cells regardless of HER2 status [67]. A recent study reports that a lapatinib-resistant oral squamous cell carcinoma cell line SAS develops sensitivity to lapatinib during sphere-formation through the activation of HER2/AKT/Cyclin D2 pathway [68]. Induced lapatinib resistance in HER2+ BC cells also shows an up-regulated Snail and Vimentin and down-regulated E-cadherin, therefor increasing intrinsic EMT capability [69].…”
Section: Her2 Blockade May Target Bcscsmentioning
confidence: 99%
“…The HSC-4 and Ca9-22 human OSCC cell line was used as an experimental model in this study. HSC-4 and Ca9-22 cells are negative for cancer stemness (41) and responsive to HGF and c-Met inhibitor SU11274 (23). Thus, the effects of curcumin on HGF-induced EMT and the invasive and migratory potential of HSC-4 and Ca9-22 cells were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Peer-reviewed version available at Cancers 2019, 11, 1552; doi:10.3390/cancers11101552 cell lines, which had little or no sensitivity to AG1478 inhibition displayed anchorage-independent growth and were able to form spheres. We investigated the EGFR-dependence of DU145, a prostate cancer cell line that could form spheres, and found that it was as resistant to AG1478 and cetuximab as the KB cell line [19]. These data suggest that anchorage-dependent growth may be linked to EGFR dependence.…”
Section: Ag1478 Suppresses Growth Of Some Cancer Cell Lines More Effementioning
confidence: 95%
“…We also showed that there were significant differences in the sensitivities of the cells to the inhibitors. In addition, none of the AG1478-sensitive cell lines were capable of anchorage-independent growth and sphere formation [19]. In contrast, the SAS and KB Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 4 September 2019 doi:10.20944/preprints201909.0037.v1…”
Section: Ag1478 Suppresses Growth Of Some Cancer Cell Lines More Effementioning
confidence: 99%
See 1 more Smart Citation